First proof of concept for full-scale, direct, low-temperature anaerobic treatment of municipal wastewater. (December 2021) - Trego, Anna Christine; Conall Holohan, B.; Keating, Ciara; Graham, Alison; O'Connor, Sandra; Gerardo, Michael; Hughes, Dermot; Ijaz, Umer Zeeshan; O'Flaherty, Vincent
Graphical abstract: Highlights: Anaerobic treatment under uniquely challenging and fluctuating conditions. Efficient BOD removal even at extreme influent concentrations and temperatures. Process supported by a dynamic, adaptable and large core microbiome. Modelling revealed several genera as 'Lottery Winners' within the microbiome. Widespread application could reduce energy use for municipal wastewater treatment. Abstract: Municipal wastewater constitutes the largest fraction of wastewater, and yet treatment processes are largely removal-based. High-rate anaerobic digestion (AD) has revolutionised the sustainability of industrial wastewater treatment and could additionally provide an alternative for municipal wastewater. While AD of dilute municipal wastewater is common in tropical regions, the low temperatures of temperate climates has resulted in slow uptake. Here, we demonstrate for the first time, direct, high-rate, low-temperature AD of low-strength municipal wastewater at full-scale. An 88 m 3 hybrid reactor was installed at the municipal wastewater treatment plant in Builth Wells, UK and operated for 290 days. Ambient temperatures ranged from 2 to 18 °C, but remained below 15 °C for > 100 days. Influent BOD fluctuated between 2 and 200 mg L -1 . However, BOD removal often reached > 85%. 16S rRNA amplicon sequencing of DNA from the biomass revealed a highly adaptable core microbiome. These findings could provide the basis for the next-generation of municipal wastewater treatment.